Prenatal multiple micronutrient supplementation impact on biochemical indicators during pregnancy and postpartum Efecto de la suplementación prenatal con micronutrimentos múltiples en indicadores bioquímicos durante el embarazo y el posparto - Armando García-Guerra; Lynnette M Neufeld; Sonia Hernández-Cordero; Juan Rivera; Reynaldo Martorell; Usha Ramakrishnan (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE: The objective of this analysis was to test the impact of daily supplementation with multiple micronutrients (MM) during pregnancy on Zn, vitamin A and folate status compared to iron only (Fe). MATERIAL AND METHODS: The study was carried out during 1997-2000 in a semi-urban community in Morelos state, Mexico. Women were randomly assigned to MM (n= 249) or Fe (n= 258) and received supplements daily (6 d/wk) under supervision by the field team from recruitment (approximately 9 weeks pregnancy) until delivery. Blood samples were collected on a sub-sample of women at baseline, 32 weeks pregnancy and one month postpartum (1PP) and assessed for serum zinc, retinol and whole blood folate (baseline and 1PP only). A breast milk sample was extracted at 1PP and assessed for retinol content. RESULT: At baseline there was no significant difference between supplementation groups in mean Zn, retinol or folate concentrations or the prevalence of deficiencies (Zn 12.2%, vitamin A 2.8%, folate 5.3%). Mean change in Zn and retinol concentrations from baseline to 32 weeks pregnancy did not differ between groups or between baseline and 1PP for Zn, retinol or folate. At 1PP, there was a tendency (p= 0.09) towards a lower prevalence of folate deficiency/depletion in the MM group (10.0%) than the Fe group (18.5%). CONCLUSIONS: MM supplementation during pregnancy did not improve zinc or vitamin A status compared to Fe only. There is some indication that folate status may have improved with MM supplementation despite low prevalence of deficiency. While lack of response in serum retinol may be explained by generally adequate status, the lack of impact on zinc status requires further exploration. OBJETIVO: Evaluar el efecto de la suplementación diaria con múltiples micronutrimentos (MM) durante el embarazo en el estado de zinc, vitamina A y folato comparado con la suplementación sólo con hierro (Fe). MATERIAL Y MÉTODOS: El estudio se realizó en una comunidad semiurbana en el estado de Morelos, México, entre 1997 y 2000. Las mujeres fueron asignadas aleatoriamente a recibir un suplemento de MM (n= 249) o Fe (n= 258) diariamente (6 días/semana), cuyo consumo fue supervisado por personal de campo, desde la evaluación basal (aproximadamente 9 semanas de gestación) hasta el parto. En una submuestra de mujeres participantes, se tomaron muestras de sangre venosa, a las 9 y 32 semanas de embarazo y al mes posparto (1PP). Se midieron las concentraciones séricas de zinc y retinol y la concentración de folato en sangre total, esta última sólo en la evaluación basal y al 1PP. Además se colectó una muestra de leche materna al 1PP, en donde se midió la concentración de retinol. RESULTADOS: En la evaluación basal no hubo diferencias significativas entre grupos en las concentraciones promedio de zinc y retinol, ni en la concentración de folato o en la prevalencia de deficiencias (Zn 12.2%, vitamina A 2.8%, folato 5.3%). El cambio promedio en zinc y retinol de la evaluación basal a la semana 32 de embarazo, no fue diferente entre grupos, tampoco entre la evaluación basal y al 1PP en zinc, retinol o folato. Al 1PP hubo una tendencia (p= 0.09) a menor prevalencia de deficiencia/depleción de folato en el grupo de MM (10.0%) que en el grupo Fe (18.5%). CONCLUSIONES: La suplementación con MM durante el embarazo no mejoró el estado de zinc y vitamina A comparada con la suplementación sólo con Fe. Sin embargo, el estado de folato puede haber mejorado con la suplementación con MM, a pesar de la baja prevalencia de deficiencia de folato. La falta de efecto en vitamina A podría ser explicada por el adecuado estado de la misma en las mujeres estudiadas y la falta de efecto en el estado de zinc requiere futura exploración.